Sir John Eliot Gardiner conducts Monteverdi's Vespro della Beata Vergine with the Monteverdi Choir and the English Baroque Soloists - Monteverdi, Claudio 1567-1643 (Wahoo Production, 2014)
Sir John Eliot Gardiner at the Versailles' Chapelle Royale! The brilliant Sir John Eliot Gardiner conducts the Monteverdi Choir, the English Baroque Soloists and the Pages du Centre de musique baroque de Versailles in one of the greatest masterpieces of the Baroque. The Vespro delle Beata Vergine was composed in 1610 in Mantua, and is now considered one of the most invaluable works in our musical heritage. Sir John Eliot Gardiner conducted the Vespers for the first time in 1964, an experience that inspired his founding of the Monteverdi Choir, a now-world-renowned vocal ensemble whose 50th anniversary celebrated with this concert. According to Gardiner, the architecture of Versailles' Chapelle Royale makes it the perfect place to perform this masterpiece: seated below the performers, the audience is placed as it would have been in Renaissance concerts, with the echos and dialogs between singers enhanced by being located at different heights. John Eliot Gardiner's 2010 performance of the Vespro at Versailles' Chapelle Royale won broad acclaim, and led to this 2014 filmed encore performance